A new microsegregation model for rapid solidification multicomponent alloys and its application to single-crystal nickel-base superalloys of laser rapid directional solidification. (1st October 2016) - Liang, Yao-Jian; Cheng, Xu; Wang, Hua-Ming
Abstract: The microsegregation in single-crystal nickel-base superalloys, which may result in many undesired precipitated phases, can be effectively reduced by rapid solidification. A new microsegregation model for rapid solidification multicomponent alloys was developed in this paper to predict the microsegregation in the single-crystal superalloys of laser rapid directional solidification and study the influence of processing parameters on the microsegregation behavior. To verify the predicted accuracy of the present model, the concentration profiles and microsegregation ranges under different processing conditions were examined and compared with those calculated by different models. Compared with previous models, this multicomponent model not only has definite physical meaning but also takes nonequilibrium solidification and dendritic tip undercooling into account. Therefore, it is suitable for a wide range of solidification conditions and can obtain better predicted results for complex multicomponent alloys. Moreover, although the microsegregation behavior depends primarily on the solidification velocity, a high temperature gradient also contributes to reducing the microsegregation. Consequently, the microsegregation can be effectively controlled by using a set of processing parameters that can obtain high temperature gradient and solidification velocity. Such a model contributes to the control of the microsegregation while determining relevant processing windows for the preparation of superalloy components using a controlled single-crystal laser processing. Graphical abstract: